PENGAWASAN DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KABUPATEN INDRAGIRI HILIR TERHADAP PENCEMARAN LIMBAH KILANG SAGU DI SUNGAI GAUNG ANAK SERKA TAHUN 2022 - Yopindra, Maulana; Tinov, Muhammad Yohamzy Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to evaluate the supervision of the Indragiri Hilir Regency Environment and Hygiene Service regarding sago mill waste pollution in the Gaung Anak Serka River in 2022. Sago mill waste pollution is a significant environmental issue, causing damage to the river ecosystem and having a negative impact on public health. A qualitative approach with descriptive methods was used in this research. Data was collected through in-depth interviews with the department, refinery managers and affected communities, plus direct observation and study of related documents. The research results show that supervision by the department is still not optimal. The causal factors are a lack of human resources and funds, as well as weak law enforcement against pollution carried out by sago factories. Even though there have been monitoring and enforcement efforts, the results have not been able to reduce pollution significantly. People still often find refinery waste polluting their water and the environment. This research recommends increasing human resources and agency budgets, as well as stricter law enforcement against violators of environmental regulations. Active community participation is also needed to increase transparency and accountability. Implementation of these recommendations is expected to reduce pollution from sago refinery waste in the Gaung Anak Serka River, creating a cleaner and healthier environment for the people of Indragiri Hilir Regency. Key words: monitoring, pollution, waste,